Relationship of Nutrient Intake and Physical Activity with Metabolic Conditions in Obesity - Putra Sugiharta, Adhika Tri; Pande Dwipayana, I Made; Indraguna Pinatih, Gde Ngurah (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: Obesity is a risk factor for several chronic diseases including hypertension, cardiovascular disease, type 2 diabetes mellitus (DMT2), dyslipidemia and other metabolic diseases. Although obese people are often associated with several chronic diseases, not all obese people experience these diseases. Method: Possible causes of changes to metabolically unhealthy obesity (OMTS) are associated with weight gain, aging, and unhealthy lifestyles. This study used a cross-sectional observational study design that included obese health workers in the RSUP Prof. dr. I.G.N.G Ngoerah Denpasar, the prevalence of OMS sufferers among obese people is around 30-40%. Resuld and Discussion: This study, 72 obese subjects were collected consecutively. Based on this number, the majority of male patients were 38 people (52.8%) and 34 women (47.2%). A total of 47 people (65.3%) belonged to the CSO group and 25 people (34.7%) were OMTS. The analysis showed that there was no association between total calories, protein and carbohydrate intake and metabolic conditions (p >0.05). High fat intake was significantly associated with the risk of poor metabolic conditions in obese individuals (RP=1,429, p=0.038). Low physical activity was positively significant with poor metabolic conditions in obesity (PR = 7.418, p = 0.004). Conclusion: This study shows that excess fat intake and less risky physical activity increase the incidence of OMTS in obese people. While other variables are total calories, carbohydrate and protein intake is not related to metabolic conditions